Analysis of Bistatic Airborne SAR data - Wendler, Michael; Krieger, Gerhard; Rodríguez-Cassolà, Marc; Horn, Ralf; Gabler, Bernd; Dubois-Fernandez, Pascale; Vaizan, Bernard; du Plessis, Oliver Ruault; Cantalloube, Hubert (European Conference on Synthetic Aperture Radar (EUSAR), 2004)
Future spaceborne SAR systems will operate in bi- and multistatic configurations to gain more information of the illuminated region. Such additional information might be the extraction of bistatic radar cross section or the simultaneous scene acquisition from different bistatic angles. Furthermore, a considerable cost reduction can be achieved by applying one radar illuminator and several passive receivers. For the definition of such SAR configurations, a bistatic airborne SAR experiment has been accomplished between the German Aerospace Center (DLR) and the French ``Office National d′Etudes et de Recherches Aérospatiales″ (ONERA) with their airborne SAR systems E-SAR and RAMSES. One of the two radar systems serves both as transmitter and receiver while the other is receiving the back-scattered radar echoes. Different configurations have been designed to achieve a maximum of useful radar data which will be investigated with respect to the bistatic angle and other issues as e.g. the applied synchronisation. The two main configurations are the along-track configuration where both aircraft are flying in close succession and the across-track configuration where both aircraft are flying alongside. The E-SAR was flying in front of RAMSES in along-track configuration for flight stability reasons. To ensure a sufficient synchronisation between the transmitting and the receiving-only system, the GPS time signal is used for the nonrecurring synchronisation of both radar systems directly before data acquisition. Several modifications have been implemented into both systems to realise this synchronisation strategy which permits a sufficient phase and timing stability of both the transmitted and received radar signals during the time of a radar data take. Some calibration targets have been set up in the test area for both mono- and bistatic radar data. This paper describes the flight configurations for the data takes of the bistatic airborne SAR experiment. The challenges that had to be met are outlined such as the platform motion which will affect the resulting common antenna footprint, or the applied synchronisation strategy. The effect of the synchronisation is shown and analysed in the bistatic radar data. The influence of the applied processing algorithm is examined by results of processed radar images and an overview of the processing status of bistatic interferometric SAR data is presented.
DLR Import::2019-04-03